2013
DOI: 10.1186/1750-1172-8-101
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Hunter syndrome (mucopolysaccharidosis type II) on health-related quality of life

Abstract: BackgroundHunter syndrome (mucopolysaccharidosis type II (MPS II)) is a rare metabolic disease that can severely compromise health, well-being and life expectancy. Little evidence has been published on the impact of MPS II on health-related quality of life (HRQL). The objective of this study was to describe this impact using the Hunter Syndrome-Functional Outcomes for Clinical Understanding Scale (HS-FOCUS) questionnaire and a range of standard validated questionnaires previously used in paediatric populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 30 publications
4
64
0
7
Order By: Relevance
“…It is important to note that only 2 publications and 2 clinical trials considered QoL as an outcome. 20,24 One of the publications was a systematic review that established QoL as one of its secondary outcomes. However, only 1 publication subsequently fulfilled the criteria to be included in the systematic review 18 and in that study QoL was not measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that only 2 publications and 2 clinical trials considered QoL as an outcome. 20,24 One of the publications was a systematic review that established QoL as one of its secondary outcomes. However, only 1 publication subsequently fulfilled the criteria to be included in the systematic review 18 and in that study QoL was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Mucopolysaccharidosis type II has been shown to be associated with significant impact on the QoL of both patients and their families. 24,27 Raluy-Callado et al used the Health Utility Index (HUI) which specifically investigated the impact of disease on hearing. They have shown that hearing is the biggest deficiency suffered by patients with MPS type II in agreement with previous publications.…”
Section: Discussionmentioning
confidence: 99%
“…The mPOMA-G showed strong concurrent validity with other validated measures of disability, activities of daily living, and physical function, which is important given that children’s usual daily activities and their performance in age-appropriate settings may be evaluated more effectively using 2 outcome measures [15]. The CHAQ and PODCI have been used frequently in children and adolescents with other conditions that affect bone, muscle, and physical activity [15, 16, 17, 18]. The PODCI and mPOMA-G association was stronger for PODCI Sports and Physical Function than Transfer and Basic Mobility, which measures shorter distance ambulation, such as climbing 1 flight of stairs and simple transfers, and had a ceiling effect for some patients with scores above the normative mean of 50 (± 10) [15, 19].…”
Section: Discussionmentioning
confidence: 99%
“…4 El considerable declive neurológico de los pacientes con la forma grave, quienes constituyen el 75% del total de casos reportados, 5 lleva a retardo mental, desórdenes conductuales y regresión del desarrollo, como fue evidenciado en nuestro paciente.…”
Section: Discussionunclassified